2018
DOI: 10.1111/codi.14342
|View full text |Cite
|
Sign up to set email alerts
|

Variations in the management of significant polyps and early colorectal cancer: results from a multicentre observational study of 383 patients

Abstract: ER is safe and feasible for treating significant colorectal polyps. Robust accreditation within the BCSP has led to improvements in management, with lower rates of SR compared with non-BCSP patients. Standardization, training in polyp assessment and treatment within a multidisciplinary team may help to select appropriate treatment strategies and improve outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 32 publications
(42 reference statements)
1
26
2
Order By: Relevance
“…Further problematic areas are the colonic flexures, any angular bends or a SPECC near, or at, the orifice of a colonic diverticulum. The right colon and caecum, where about a third of SPECC lesions are located , may be difficult to access (Fig. ).…”
Section: Colonic Speccmentioning
confidence: 99%
See 1 more Smart Citation
“…Further problematic areas are the colonic flexures, any angular bends or a SPECC near, or at, the orifice of a colonic diverticulum. The right colon and caecum, where about a third of SPECC lesions are located , may be difficult to access (Fig. ).…”
Section: Colonic Speccmentioning
confidence: 99%
“…It is pertinent to note that the anatomical location of a SPECC is similar to that of colon and rectal cancer. A recent multicentre UK study on 383 SPECC lesions reported that 33% were classified as originating in the rectum, 27% in the left colon and 29% in the ascending colon and caecum .…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the reliance on superficial biopsies to diagnose malignancy in a polyp is also contentious and may lead to suboptimal treatment if endoscopic resection is recommended. Multiple studies have shown that even with benign superficial biopsies, the risk of finding an unexpected cancer in the post‐treatment specimen is approximately 10%, highlighting the importance of complementary assessment tools to aid decision making .…”
Section: Endoscopic Polyp Assessmentmentioning
confidence: 99%
“…One of the overarching themes was that 'decisions are more important than incisions' when it comes to optimal treatment of a SPECC, a concept we had published previously on the overview of our experience with the English National Low Rectal Cancer Development Program [8]. In conjunction with the SPECC Program we have recently reported the variations in the management of significant polyps and early colorectal cancers on a multicentre observational study of 383 patients [9]. All 383 patients had polypoid lesions greater than 20 mm in size and were detected either at bowel cancer screening (108/383 ¼ 28%) or at endoscopy for either symptomatic patients or colonic surveillance in 275 (62%).…”
Section: Specc Workhop Programmentioning
confidence: 99%
“…The unexpected cancer detection rate in these SPECC lesions was 10%, similar to previous publications. A significant original observation was that SPECC lesions detected in the Bowel Cancer Screening Program were significantly more likely to have successful endoscopic resection suggesting that endoscopic skill and adequate time and resources were associated with more effective and safer treatments [9].…”
Section: Specc Workhop Programmentioning
confidence: 99%